Mesoporous Titania‐Alumina Mixed Oxide: A Heterogeneous Nanocatalyst for the Synthesis of 2‐Substituted Benzimidazoles, Benzothiazoles and Benzoxazoles. Issue 39 (22nd October 2018) - Bahrami, Kiumars; Bakhtiarian, Mohsen
Abstract: Mesoporous titania‐alumina mixed oxide (MTAMO) was synthesized by sol‐gel pathway using sodium dodecyl sulfate as a structure directing agent and successfully employed as a highly efficient nanocatalyst for the synthesis of 2‐substituted benzimidazoles, benzothiazoles, and benzoxazoles using 30% H2 O2 as a green oxidant. The described methodology offers the benefits of operational simplicity, excellent yields, short reaction times and mild conditions. The catalyst characterized by various techniques like Fourier transform infrared (FT‐IR) spectroscopy, X‐ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), energy dispersive X‐ray (EDX) and N2 adsorption‐desorption. Abstract : Mesoporous titania‐alumina mixed oxide (MTAMO) nanocatalyst was synthesized by sol‐gel pathway using sodium dodecyl sulfate as a structure directing agent and successfully employed as a highly efficient nanocatalyst for the synthesis of 2‐substituted benzimidazoles, benzothiazoles, and benzoxazoles using 30% H2 O2 as a green oxidant. The described methodology offers the benefits of operational simplicity, excellent yields, short reaction times and mild conditions.